POTENSI MEDIA AGAR PISANG MAS SEBAGAI MEDIA TUMBUH Staphylococcus aureus DAN Aspergillus niger - Amaliyah Nurul Hidayah; Ayuk Lestari; Mikhania Christiningtyas Eryani; Siti Nur Azizah (Florea : Jurnal Biologi dan Pembelajarannya, 2022)
The high cost of instant culture media on the market has become the background of research to develop Mas banana (Musa acuminata Colla) Agar as a culture medium for Staphylococcus aureus and Aspergillus niger. Culture media is a mixture of nutrients or food substances needed by microorganisms for their growth. The purpose of this study was to determine the potential of Mas banana Agar (Musa acuminata Colla) at various concentrations of 2%, 4%, 6%, and 8% on the number of Staphylococcus aureus colony and Aspergillus niger micellium diameter. The type of research used was experimental research. The research stages were making Mas banana flour, prepared suspension of Staphylococcus aureus and Aspergillus niger, prepared Mas banana Agar, bacterial culture (spread method) incubated for 24hours at 37Â°C and mold (dot method) were incubated for 7 days at 37Â°C. Based on the results, S. aureus colonies on Mas banana Agar at 2%, 4%, 6% and 8% were 43.67 colonies, 52 colonies, 17.33 colonies and 7.67 colonies respectively. The average of Aspergillus niger mycelium diameter at 2%, 4%, 6% and 8% were 11.43 mm, 12.63 mm, 25.26 mm and 62.33 mm respectively. It can be concluded that Staphylococcus aureus and Aspergillus niger cultures growth on Mas banana Agar (Musa acuminata Colla) at various concentrations of 2%, 4%, 6%, 8%.